Combustibility of fuel material for forest species - Borges, César Henrique Alves; Souto, Patrícia Carneiro; Nascimento Neto, João Henrique do; Souto, Jacob Silva; Araujo, Emmanoella Costa Guaraná; Silva, Thiago Cardoso (Scientific Electronic Archives, 2021)
The work aimed to characterize the flammability of different forest species. The combustible materials were collected in two places with different phytophysiognomies, both in the state of Paraíba, Brazil. The plant materials used were: Poincianella bracteosa, Aspidosperma pyrifolium, Luetzelburgia auriculata, Croton sonderianus and Pinus sp. acicles and branches were used as a control. The burns were carried out in an open area located in the forest nursery, where approximately 0.5 kg of material was weighed on a precision scale. After the organization of the plots, the thickness of each pile was measured with the aid of a ruler graduated in centimeters. To determine the speed of fire propagation, the average time spent by the fire front (m s-1) to travel pre-established distances during the fires was measured. It is observed that among the studied materials, Pinus was the one that presented the lowest weight after burning the material and was the species that presented the highest temperature after burning, followed by C. sonderianus and A. pyrifolium. Before burning, all species showed behaviors, ranging from 30 to 33 °C. It is extremely important to replicate this type of study in forest areas, since the variations found can influence the results. The effect of burning combustible materials on soil temperature was greater in treatments with Pinus and C. sonderianus.